PENGARUH TEKNIK AUDIT BERBANTUAN KOMPUTER, DUE PROFESSIONALISME CARE, AKUNTABILITAS, KECERDASAN SPIRITUAL PADA KUALITAS AUDIT - Amerthajaya, Nyoman Tri Nurasta; Aryani M, Ni Ketut Lely (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect TABK , due professionalisme care , accountability , and spiritual intelligence on audit quality in BPK RI Representative Bali Province . The data collection is done by distributing questionnaires to all auditors in BPK RI Representative Bali Province as respondents using saturation sampling technique sampling . The analysis technique used is multiple linear regression . The results of multiple linear regression analysis by observing Adjusted R2 value , indicating that the variable quality of the audit can be explained by the variable TABK , due care professionalism , accountability and spiritual intelligence by 66 % . Testing the hypothesis with t statistical test showed that the variables TABK , due care professionalism , accountability , spiritual intelligence significant positive effect on audit quality , while the remaining 34 % is influenced by other variables not included in the model study.
Keywords: Computer Assisted Audit Techniques, Due Professionalisme care, Accountability, Spiritual Intelligence